A Novel CCAG Hydrogel: The Mechanical Strength and Crosslinking Densities - Li, Xian; Fan, Daidi (Asian Journal of Chemistry, 2014)
In this study, swelling behaviour and mechanical properties of the CS-HLC-HA/b-GP (chitosan-human like collagen-hyaluronic acid/b-sodium glycerophosphate) hydrogels, were investigated. The pH/temperature sensitive CCAG (CS-HLC-HA/b-GP) hydrogels were successfully synthesized by a combination of CCA (CS-HLC-HA) and b-GP by self-assemble technique. Compression-strain measurements were used to analyze the mechanical properties of the hydrogels. It was found that increasing the amount of hyaluronic acid comonomer in the gel structure increases the compression modulus of the materials. The results of mechanical measurements were used to characterize the network structure of the hydrogels, namely the effective crosslinking density (r). It was found that r increasing calculated from the initial amount of hyaluronic acid used for hydrogel synthesis. These hydrogels demonstrated dual sensitivity to both pH and temperature. It showed that the pH-sensitive or temperature-sensitive phase transition behaviour of the gels can be changed by changing the temperature or pH of the swelling medium at constant hydrogel composition. Finally, the results of equilibrium swelling and compression-strain measurements were used to calculate the interaction parameters of these hydrogels using a gel strength instrument.